Protective Effect of Crocin on Immune Checkpoint Inhibitors-Related Myocarditis Through Inhibiting NLRP3 Mediated Pyroptosis in Cardiomyocytes via NF-κB Pathway - Zhang H; Lin J; Shen Y; Pan J; Wang C; Cheng L (Dove Medical Press, 2022)
Hui Zhang,1,* Jinyi Lin,2,* Yihui Shen,1 Jianan Pan,3 Chunhui Wang,4 Leilei Cheng1 1Department of Echocardiography, Zhongshan Hospital, Fudan University, Shanghai Institute of Cardiovascular Diseases, Shanghai Institute of Medical Imaging, Shanghai, People's Republic of China; 2Department of Cardiology, Zhongshan Hospital, Fudan University, Shanghai Institute of Cardiovascular Diseases, Shanghai, People's Republic of China; 3Department of Cardiology, Shanghai Ninth People's Hospital, Shanghai JiaoTong University School of Medicine, Shanghai, People's Republic of China; 4Department of Pharmacy, Zhongshan Hospital, Fudan University, Shanghai, People's Republic of China*These authors contributed equally to this workCorrespondence: Leilei Cheng, Department of Echocardiography, Zhongshan Hospital, Fudan University, Shanghai Institute of Cardiovascular Diseases, Shanghai Institute of Medical Imaging, Shanghai, 200032, People's Republic of China, Fax +86-21-51217561, Email cheng.leilei@zs-hospital.sh.cnPurpose: Immune checkpoint inhibitors (ICIs)-related myocarditis is now one of the most critical immune-related adverse effects (irAEs) in tumor immunotherapy, which has raised great concern in cardio-oncology. The pathogenesis involved in cardiac injury remains elusive. Crocin, the main component of saffron, has shown distinct functions in cardioprotective and anti-inflammation properties. We therefore aimed to investigate the potential effect of crocin on the protection of ICIs-related myocarditis and its underlying molecular mechanism.Methods: We immunized the BALB/c mice with murine cardiac troponin I (cTnI) peptide and additionally gave anti-mouse programmed death 1 (PD-1) to induce the mouse model of ICIs-related myocarditis. Mice were treated with crocin at different dosages. In vitro, HL-1 cells were pre-incubated with crocin at different concentrations and then stimulated with lipopolysaccharide (LPS). Myocardial contractile functions, myocardial inflammation and fibrosis, and myocardial injury were assessed. The expressions of pyroptosis-related proteins and nuclear factor-κB (NF-κB) pathway were evaluated.Results: Crocin treatment could partially reverse the ICIs-related myocarditis in terms of improving heart function, ameliorating inflammation and fibrosis in the myocardium, and alleviating myocardial injury. Mechanistically, ICIs administration significantly activated pyrin domain-containing protein 3 (NLRP3) inflammasome in cardiomyocytes. Crocin treatments significantly downregulated the expression of NLRP3, cleaved gasdermin D (GSDMD), cleaved caspase1, interleukin-1β (IL-1β), and IL-18. Besides, crocin inhibited the activation of NF-κB pathway, which performed as reducing the phosphorylation of p-NF-kappa-B inhibitor-α (p-IκBα), degradation of IκBα, phosphorylation of p65 and p65 DNA binding activity both in vivo and in vitro.Conclusion: By reversing the pyroptosis in cardiomyocytes, crocin treatment in a mouse model exerted great potential to aid in the prevention of ICIs-related myocarditis from a novel target.Graphical Abstract: Keywords: cardio-oncology, immune checkpoint inhibitors, autoimmune myocarditis, programmed death 1, immune-related adverse effects